Cell Adaptations of Rhodococci to Pharmaceutical Pollutants - Tyumina, Elena A.; Bazhutin, Grigory A.; Ivshina, Irina B. (KnE Life Sciences, 2022)
Against the background of atense environmental situation, the risk of drug pollution in the natural environment is steadily increasing. Pharmaceuticals entering open ecosystems can cause toxic effects in wildlife from molecular to population levels. The aim of this research was to examine the impact of pharmaceutical pollutants on rhodococci, which are typical representatives of soil actinobacteria and active biodegraders of these compounds. The pharmaceutical products used in this research werediclofenac sodium and ibuprofen, which are non-steroidal anti-inflammatory drugs (NSAIDs) that are widely used and frequently found in the environment. The most common cell adaptations of rhodococci to the effects of NSAIDs were changes in zeta potential, catalase activity, morphometric parameters and degree of hydrophobicity; elevated contents of total cellular lipids; and the formation of cell conglomerates. The findings demonstrated the adaptation mechanisms of rhodococci and their increased resistance to the toxic effects of the pharmaceutical pollutants. Keywords: pharmaceutical pollutants, NSAIDs, diclofenac, ibuprofen, cell responses, Rhodococcus